Elaboration of a psychological instrument to provide vocational guidance to the students who finish secondary in Lima - Peru - Chávez, Hilda (2019)
It was a technology, descriptive, comparative and transectional research that aimed to develop a psychological instrument oriented to obtain the professional profile of the different areas to which pre-university students apply to the universities of Lima, according to the variables preferences vocational and multiple intelligences. In order to achieve the aforementioned objective, a psychological vocation orientation instrument was elaborated whose structure includes the following professional areas: Health Sciences; Basic sciences; Engineering; Economics and Management Sciences; and, Humanities and Legal and Social Sciences. Whose results were reflected in: predominant professional area, chosen professional area and preferred professional area. The processing of the data obtained was developed using both the MS Excel Spreadsheet and the 24 version of the SPSS Statistical Software. For the analysis of these results, some control variables were used; such as: age, gender, type of educational institution of origin and district of residence. The evidence of validity was determined by content validity by expert judgment, with V of Aiken equal to 0.92, and the reliability for internal consistency through the Cronbach's Alpha coefficient α = 0.72; and by halves for the dimensions which oscillated between 0.40 and 0.74.